2022
DOI: 10.1175/jcli-d-21-0391.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Disabling Cloud Radiative Feedbacks Change Spatial Patterns of Surface Greenhouse Warming and Cooling?

Abstract: The processes controlling idealized warming and cooling patterns are examined in 150 year-long fully coupled Community Earth System Model version 1 (CESM1) experiments under abrupt CO2 forcing. By simulation end, 2xCO2 global warming was 20% larger than 0.5xCO2 global cooling. Not only was the absolute global effective radiative forcing ∼10% larger for 2xCO2 than for 0.5xCO2, global feedbacks were also less negative for 2xCO2 than for 0.5xCO2. Specifically, more positive shortwave cloud feedbacks led to more 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 74 publications
(67 reference statements)
5
21
0
Order By: Relevance
“…Note that while our focus is on the atmospheric response to a given SST pattern, causality can work in both directions. For example, cloud feedback has been shown to have an impact on the pattern of tropical Pacific SST changes in models (Chalmers et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Note that while our focus is on the atmospheric response to a given SST pattern, causality can work in both directions. For example, cloud feedback has been shown to have an impact on the pattern of tropical Pacific SST changes in models (Chalmers et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, CO 2 is varied from 1/8× to 8×PI values, to test the CO 2 symmetry of the climate system response to comparable increased and decreased CO 2 . While we are not the first ones to perform such symmetric CO 2 runs (Chalmers et al., 2022; Colman & McAvaney, 2009; Hansen et al., 2005; Russell et al., 2013), here we explore (a) a larger CO 2 range than previously considered, (b) we do so using two different fully coupled climate models and, most importantly, (c) we perform the experiments with both abrupt and transient CO 2 runs.…”
Section: Introductionmentioning
confidence: 99%
“…The question thus remains: is the climate system response symmetric across a broad range of positive (warm) and negative (cold) CO 2 forcings? The question of symmetry was examined recently by Chalmers et al (2022), who compared 1/2× and 2×CO 2 simulations performed with the CESM1-CAM5 model, and found that global surface temperatures warm 20% more than they cool. Roughly 50% of this asymmetry was shown to derive from an asymmetry in CO 2 radiative forcing; the rest was associated with differences in feedbacks which, interestingly, were found not to be related to clouds.…”
mentioning
confidence: 99%
“…However, when comparing halving and doubling of CO2 from pre-industrial conditions, either little differences of global λ cl were found in the Australian BRMC model (e.g. Colman and McAvaney, 2009), or weaker λ cl in abrupt0p5xCO2 experiment than abrupt2xCO2 experiment in CESM1.2 (Chalmers et al, 2022).…”
Section: Single-model Cloud Feedbacksmentioning
confidence: 94%